2021
DOI: 10.3390/rs13040717
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Study of FORMOSAT-7/COSMIC-2 Radio Occultation Data in the Troposphere

Abstract: This study investigates the Global Navigation Satellite System (GNSS) radio occultation (RO) data from FORMOSAT-7/COSMIC-2 (FS7/C2), which provides considerably more and deeper profiles at lower latitudes than those from the former FORMOSAT-3/COSMIC (FS3/C). The statistical analysis of six-month RO data shows that the rate of penetration depth below 1 km height within ±45° latitudes can reach 80% for FS7/C2, significantly higher than 40% for FS3/C. For verification, FS7/C2 RO data are compared with the observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…To study the sensitivity of the assimilation system to these refractivity differences, Equation 2 along with the corresponding tangent linear and adjoint codes, is implemented in WRFDA, as discussed in Appendix A. their results show that C2 data quality in terms of stability, precision, and accuracy is comparable to that from C1. Chen et al (2021) showed the high quality of C2 temperature and specific humidity profiles (wetPf2) obtained from a 1D-Var retrieval. Here we assess the C2 refractivity observations for an extended period (October 2019 to December 2020).…”
Section: Gnss Ro Techniquementioning
confidence: 92%
See 1 more Smart Citation
“…To study the sensitivity of the assimilation system to these refractivity differences, Equation 2 along with the corresponding tangent linear and adjoint codes, is implemented in WRFDA, as discussed in Appendix A. their results show that C2 data quality in terms of stability, precision, and accuracy is comparable to that from C1. Chen et al (2021) showed the high quality of C2 temperature and specific humidity profiles (wetPf2) obtained from a 1D-Var retrieval. Here we assess the C2 refractivity observations for an extended period (October 2019 to December 2020).…”
Section: Gnss Ro Techniquementioning
confidence: 92%
“…Chen et al. (2021) showed the high quality of C2 temperature and specific humidity profiles (wetPf2) obtained from a 1D‐Var retrieval. Here we assess the C2 refractivity observations for an extended period (October 2019 to December 2020).…”
Section: Gnss Ro Techniquementioning
confidence: 99%
“…Due to the proven significant influence of TEC on the quality of the received satellite signal, much attention has been focused on TEC prediction, e.g., by using artificial neural networks [31][32][33][34]. Another important field of study is radio occultation technique, which is used both for studying ionosphere, space weather, and neutral atmosphere [35,36]. The troposphere, on the other hand, is the lowest and the thinnest layer of the atmosphere.…”
Section: Research Problemmentioning
confidence: 99%
“…The FORMOsa SATellite mission-7/Constellation Observing System for the Meteorology, Ionosphere, and Climate mission-2 (FORMOSAT-7/COSMIC-2, hereafter FS7/C2), which is a follow-on mission of FORMOSAT-3/COSMIC (FS3/C), was launched on 25 June 2019, and it now can provide more than 5000 RO soundings per day within the ±45° latitudinal region. The FS7/C2 data provide not only a larger data amount but also penetrate farther to near the surface than the FS3/C data, and qualities of both data are comparable (e.g., [7][8][9]). For example, Ho et al [8] compared the FORMOSAT-7/COSMIC-2 RO data and the radiosonde observations, and the mean difference and standard deviation (STD) of the refractivity were about 0.34% and 1.84%, respectively.…”
Section: Introductionmentioning
confidence: 99%